The public perception of crime prevalence, newspaper readership and ‘mean world’ attitudes - O'Connell, Michael (Legal and criminological psychology, 1996)
Surveying an Irish sample, the authors asked respondents (N=623) to give their views on the seriousness of and appropriate penalties for 10 offence scenarios. They also assessed the respondents' risk perception of crime by asking for estimates of the prevalence of the same 10 offence scenarios compared to five years previously. Experience of crime victimization and socio-demographic data were also gathered. Beliefs about crime prevalence were found to be independent of official crime rates, personal experience of victimization and some socio-demographic categories. Sex, age and newspaper readership were found to be the strongest predictors of crime prevalence estimates. Additional support for the role of the media was suggested by the clustering of a number of ‘mean world’ attitudes towards crime.